Ветеран победы: доцент Новикова М.И. - Казарин, В.П.; Новикова, М.И. (Культура народов Причерноморья, 2014)
В статье рассмотрен творческий и общественный путь М.И. Новиковой (1917-2007) – доцента и многолетней заведующей кафедрой русской и зарубежной литературы Крымского федерального университета (ранее Таврического национального, ещё раньше – Симферопольского государственного университета), ветерана Великой Отечественной войны, члена Союза писателей и Союза театральных деятелей СССР, отличника народного просвещения. Охвачен период с 1933 года; в обзор включены литературоведческие, театроведческие, методические и публицистические работы М.И. Новиковой, а также её художественные произведения (рассказы, повести, романы) – всего 286 позиций. Освещена общественная деятельность М.И. Новиковой в социокультурном контексте Крыма, университета, кафедры. У статті розглянуто творчій та суспільний шлях М.І. Новикової (1917-2007) – доцента та багатолітньої завідувачки кафедри російської та зарубіжної літератури Кримського федерального університету (раніше Таврійського національного, ще раніше – Сімферопольського державного університету), ветерана Великої Вітчизняної війни, члена Спілки письменників та Спілки театральних діячів СРСР, відмінника народної просвіти. Охоплений період з 1933 року; в огляд включені літературознавчі, театрознавчі, методичні та публіцистичні праці М.І. Новикової, а також її художні твори (оповіді, повісті, романи) – усього 286 позицій. Висвітлена суспільна діяльність М.І. Новикової в соціокультурному контексті Криму, університету, кафедри. The paper deals with M.I. Novikova’s (1917-2007) creative and social activities as a docent and head of Russian and World Literature Department (now Crimean, the latest Tavrida, or Simferopol University). M.I. Novikova was also Veteran of World War 2 (the Great Patriotic War), partaking in Literary, Theatre and Didactic Studies, publicistic and belletre activities. Her life-long evolution has been regarded within Crimean and University social and cultural context. The paper covers the period from the 30-es up to the 90-es. It reviews her articles, monographs, essays, stories and novels, 286 positions on the whole. Special stress is put upon her war-time subjects: military and resistance memoirs, including her own diary (1941-1945). Her contacts with Crimean veterans, or heroes of partisan movement have been also registered. The post-war times, with their education system, literary, arts, agricultural and urban life gave a unique ground for M.I. Novikova’s personal and artistic experience.